Insecticide resistance development in Culex quinquefasciatus (Say), Aedes aegypti (L.) and Aedes albopictus (Skuse) larvae against malathion, permethrin and temephos. - Hamdan, H.; Sofian-Azirun, Mohd; Nazni, W.A.; Lee, H.L. (2005)

(untitled)
Laboratory-bred females of Culex quinquefasciatus, Aedes aegypti and Aedes albopictus from the insectarium, Unit of Medical Entomology, Institute for Medical Research were used in the experiment. The late third stage of the F0 larvae which survived the high selection pressure of malathion, permethrin and temephos were reared and colonies were established from adults that emerged. Cx. quinquefasciatus larvae were subjected to selection by malathion and permethrin for 40 generations, Ae. aegypti larvae to malathion, permethrin and temephos for 32 generations and Ae. albopictus larvae were selected against malathion and permethrin for 32 generations and 20 generations against temephos. The rate of resistance development was measured by LC50 value. Cx. quinquefasciatus larvae developed higher resistance to malathion and permethrin compared to Ae. aegypti and Ae. albopictus. On the whole, permethrin resistance developed at a faster rate than malathion and temephos.